2012
DOI: 10.1111/apt.12089
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication in Western Australia using novel quadruple therapy combinations

Abstract: SUMMARY BackgroundHelicobacter pylori eradication rates with standard triple therapy are declining worldwide. The optimal management of H. pylori is evolving and new treatment combinations for antibiotic resistant H. pylori strains are required, especially for patients with penicillin allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 59 publications
0
56
2
Order By: Relevance
“…Th ere are no published studies of its use as a salvage therapy in North America. Nonrandomized studies from Russia, Ireland and Australia utilizing three-and four-drug regimens, have reported ITT eradication rates ranging from 60 to 86% for furazolidone salvage regimens (211)(212)(213). Th e lack of RCTs reporting the comparative effi cacy of furazolidone salvage therapy and its potential for harms including hypotension, urticaria, gastrointestinal symptoms, and reversible hemolysis make it impossible to recommend its use as a salvage treatment.…”
Section: High-dose Dual Regimen With Amoxicillinmentioning
confidence: 99%
“…Th ere are no published studies of its use as a salvage therapy in North America. Nonrandomized studies from Russia, Ireland and Australia utilizing three-and four-drug regimens, have reported ITT eradication rates ranging from 60 to 86% for furazolidone salvage regimens (211)(212)(213). Th e lack of RCTs reporting the comparative effi cacy of furazolidone salvage therapy and its potential for harms including hypotension, urticaria, gastrointestinal symptoms, and reversible hemolysis make it impossible to recommend its use as a salvage treatment.…”
Section: High-dose Dual Regimen With Amoxicillinmentioning
confidence: 99%
“…Fiorini and colleagues reported mild-tomoderate side effects in 15% and 20% of patients in each treatment arm; however, all patients complied with at least 90% of the treatment [Fiorini et al 2013]. Gasbarrini and colleagues, Tay and coworkers and Yahav's group did not mention the number of patients with adverse events, though the latter author reported a treatment compliance of 97% [Gasbarrini et al 2000;Tay et al 2012;Yahav et al 2006].…”
Section: Safety and Side Effectsmentioning
confidence: 99%
“…This suggested that antibiotics together with proton pump inhibitors could be the optimal treatment for gastro-duodenal ulcers and dyspepsia in general, a simple and apparently benign approach that is only sometimes confounded by antibiotic resistance (Tay et al 2012).…”
Section: Helicobacter Pylorimentioning
confidence: 99%